(3GdYHGH aj GddZIs - (3GdMSf Hf eMeO Hf GdMSf Hf MjOQ GdYOhj GdYeQj GdUGZGfj GdMfaj QVqj GdOjf,J (B650 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg hbdO ef GdTQGH ai Lhag EPG TQH hGdbdO di GdTF Ydi GdTF s
(3BNQgG (B:s
(3GdeGA Ke UHGg ai GdMhV ai GdSbG A s
(3GdfSNI HgG MhGTs
(3gPG GdeLdO ZjQ eQJHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B232 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B279s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GddZIs